Evaluation of the Online Media Advertising Cost Calculation System Using the Cost Per Click and Cost Per Mille Methods - Master Edison Siregar (LPPM Universitas Bhinneka Nusantara, 2026)
Online advertising platforms commonly employ Cost-Per-Click (CPC) and Cost-Per-Thousand-Impressions (CPM) models to determine advertiser fees based on user engagement and exposure metrics. While these pricing arrangements are mathematically simple, ensuring calculation accuracy and the scalability of the costing system is crucial for maintaining financial transparency and operational security. This study examines an online media advertising costing system using CPC and CPM methods through a structured system validation approach. The evaluation includes calculation verification, consistency testing against manual calculations, performance benchmarking, scalability assessment, and sensitivity analysis. A simulated dataset of 100 ad records was used to assess the system's accuracy and behavioral performance. The results demonstrate no calculation deviation between manual and system outputs, predictable linear scalability, and logistic revenue sensitivity under rate variations. These findings indicate that the evaluated system exhibits reliable calculation performance under controlled conditions. This study contributes to the evaluation of applied information systems by providing a structured methodology for validating ad collection systems.